2019
DOI: 10.1186/s12882-018-1186-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term incense use and the risk of end-stage renal disease among Chinese in Singapore: the Singapore Chinese health study

Abstract: BackgroundExperimental studies have shown that exposure to incense burning may have deleterious effects on kidney function and architecture. However, the association between chronic exposure to incense smoke and risk of end-stage renal disease (ESRD) has not been reported in epidemiologic studies.MethodsWe investigated this association in the Singapore Chinese Health Study, a prospective population-based cohort of 63,257 Chinese men and women of 45–74 years of age in Singapore during recruitment from 1993 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…This risk further increased in cases of daily users with more than 20 years of incense burning. 19 Consistently, the adverse effects of chronic exposure to incense smoke on kidney function and architecture were observed in previous experimental study. In particular, exposed rats exhibited significantly persistent inflammation as well as abnormal functions and ultrastructural changes of kidney.…”
Section: Evidence-based Associations Between Incense Burning and Health Effectssupporting
confidence: 84%
See 1 more Smart Citation
“…This risk further increased in cases of daily users with more than 20 years of incense burning. 19 Consistently, the adverse effects of chronic exposure to incense smoke on kidney function and architecture were observed in previous experimental study. In particular, exposed rats exhibited significantly persistent inflammation as well as abnormal functions and ultrastructural changes of kidney.…”
Section: Evidence-based Associations Between Incense Burning and Health Effectssupporting
confidence: 84%
“… 14 In contrast, lesser effects of incense burning on kidney function was observed in smokers who were already exposed to the strong and harmful substances from cigarette smoking as compared to non-smokers. 19 In addition to incense smoke, incense stick ash is also of health concern as a product of burning process that needs more understanding. Summing up all the potential effects of incense use on human health and environmental ambience, further investigations in the future are desirable to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant increase in tissue gene expression of both CYP1A1 and CYP1A2 were noted in incense exposed rats (19) . In Singapore, the long-term daily exposure of the Chinese population to domestic incense burning has been associated with an increased development of end stage renal disease (52) .…”
Section: Inflammationmentioning
confidence: 99%
“…Many investigations (Lorena 2020;Geng et al, 2019;Al-Yasiry et al, 2016;Vudanna et al, 2016;Al-Hararasi et al, 2014;Zarshenas et al, 2013) observed these incenses (a) to alleviate stress and emotion, (b) boost and balance immune and hormone system, (c) anti-aging properties, (d) catalyze the secretion of digestive enzymes and, (e) decrease inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the local statutory bodies did not undertake any precautionary measures or standardized regulations to burn incense. Nonetheless, the effects of burning such incenses in Kuwait were least described (Wolter 2015;Geng et al, 2019;Amoatey et al, 2018;OSHA 2017;Yuan et al, 2020;Bahloul and Gevao 2014;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%